2018
DOI: 10.1111/ejn.14182
|View full text |Cite
|
Sign up to set email alerts
|

The unlikely partnership between LRRK2 and α‐synuclein in Parkinson's disease

Abstract: Our understanding of the mechanisms underlying Parkinson's disease, the once archetypical nongenetic neurogenerative disorder, has dramatically increased with the identification of α‐synuclein and LRRK2 pathogenic mutations. While α‐synuclein protein composes the aggregates that can spread through much of the brain in disease, LRRK2 encodes a multidomain dual‐enzyme distinct from any other protein linked to neurodegeneration. In this review, we discuss emergent datasets from multiple model systems that suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 263 publications
(319 reference statements)
1
36
1
Order By: Relevance
“…The toxicity of α‐Syn may also be mediated through its interaction with LRRK2 kinase. Common protein interactors may regulate or mediate α‐Syn and LRRK2 interaction in PD …”
Section: Mitophagy and Neurodegenerative Diseasesmentioning
confidence: 99%
“…The toxicity of α‐Syn may also be mediated through its interaction with LRRK2 kinase. Common protein interactors may regulate or mediate α‐Syn and LRRK2 interaction in PD …”
Section: Mitophagy and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Interestingly, we noticed the presence of a peculiar LC3 staining pattern in nigra, cortex, and hippocampus of hG2091S mice suggesting the presence of perinuclear pale bodies (supplementary figure 1). It has been suggested that LRRK2 mutations promote α-synuclein aggregation (Cresto et al 2019;MacIsaac et al 2020). Therefore we studied the distribution of α-synuclein in different brain areas of 6-month old wild-type and hG2019S mice.…”
Section: G2019s Mutation Correlates With the Deposition Of Nsf Aggregmentioning
confidence: 99%
“…The cases of patients harboring the G2019S and other mutations are clinically indistinguishable from idiopathic PD cases, including the presence of Lewy bodies (LBs) in most cases [14,15]. Although G2019S patients show similar clinical manifestations as those of sporadic patients [16], several studies have shown subtle differences [17,18]. Some have reported the presence of LBs in symptomatic LRRK2 mutation carriers and LRRK2 can be found in LBs [19], although this is still a subject of debate, as other neuropathological studies have instead reported the absence of detectable LBs in a sub-population of PD patients with LRRK2 mutations [20].…”
Section: Introductionmentioning
confidence: 99%
“…The central role of α-syn in PD pathogenesis has led to the hypothesis of a functional (and possibly physical) interaction between LRRK2 and α-syn [for a review [25]. Indeed, LRRK2 toxicity may require the presence of α-syn and, conversely, the presence of variant/mutant LRRK2 could increase the risk and/or impact of α-synucleopathy in PD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation